A novel biosensor with high signal‐to‐noise ratio for real‐time measurement of dopamine levels in vivo. Issue 5 (1st November 2017) - Ishida, Akimasa; Imamura, Atsushi; Ueda, Yoshitomo; Shimizu, Takeshi; Marumoto, Ryosuke; Jung, Cha‐Gyun; Hida, Hideki
Abstract: Fast‐scan cyclic voltammetry (FSCV) is an established method for measuring dopamine (DA) levels in the brain in real time. However, it is difficult to discriminate DA from other monoamines such as serotonin (5‐hydroxytryptamine, 5‐HT) and norepinephrine (NE). We report a novel DA‐specific biosensor consisting of a carbon‐fiber electrode coated with an ion‐exchange membrane, a layer containing monoamine oxidase B, and a cellulose membrane. We performed FSCV using the probe to monitor the amount of DA in vitro and in vivo. First, we measured currents in vitro in phosphate‐buffered saline as we added one micromole each of DA, 5‐HT, and NE. The results confirmed that the biosensor selectively detected DA. Next, we implanted the probe in the striatum of male rats to investigate whether it could selectively detect changes in the DA content in vivo. The probe detected both the tonic change induced by methamphetamine administration and the phasic change induced by electrical stimulation of the medial forebrain bundle. In contrast, the electrode in the 6‐hydroxydopamine–lesioned striatum did not respond to systemic selective serotonin or serotonin/norepinephrine reuptake inhibitors, confirming its selectivity. Furthermore, the probe in the striatum could still detect changes in the DA level 1 week after electrode implantation. The results suggest that the novel biosensor can measure real‐time changes in DA levels in vivo with a relatively high signal‐to‐noise ratio. Abstract : A novel, MAO‐B‐contained double‐layered electrode was developed for real‐time measurement of dopamine. The biosensor can discriminate dopamine from other monoamines with high signal‐to‐noise ratio in vitro and in vivo.